2023
DOI: 10.1177/21501351231154207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Type of Enteral Feeds on Early Postoperative Outcomes After Congenital Heart Surgery in Neonates and Young Infants: A Single Center Experience in a Limited Resource Environment

Abstract: Background: Breast milk is known to prevent infections and is recommended for enteral feeding of infants after congenital heart surgery (CHS). During the Covid-19 pandemic, expressed breast milk (EBM) was not always available; hence, feeding after CHS was maintained with EBM or infant formula (IF) or both; we evaluated the impact of enteral feed type on early postoperative outcomes after CHS. Methods: In a prospective observational study, consecutive neonates and infants <4 months undergoing CHS were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…HM has been associated with lower rates of sepsis 16 , 17 , 19 , 30 , 72 , 73 and infection 32 for preterm infants and infants with surgical gastrointestinal anomalies, with protective mechanisms likely similar to those previously described for NEC (eg, reduced gut dysbiosis with subsequent lower risk of pathogenic gut bacteria translocation 74 ). A 2023 study by Ghosh et al 75 reported a 2.58‐fold increase in the odds of postoperative infection (ie, bloodstream infection, surgical site infection, ventilator‐associated pneumonia [ P =0.040]) associated with exclusive infant formula, compared with exclusive HM, for infants undergoing cardiac surgery at a single center in India. This study, however, is limited in that infants in the exclusive HM group were substantially older (ie, median 60 days versus 15 days) and underwent less complicated procedures, on average.…”
Section: Discussionmentioning
confidence: 99%
“…HM has been associated with lower rates of sepsis 16 , 17 , 19 , 30 , 72 , 73 and infection 32 for preterm infants and infants with surgical gastrointestinal anomalies, with protective mechanisms likely similar to those previously described for NEC (eg, reduced gut dysbiosis with subsequent lower risk of pathogenic gut bacteria translocation 74 ). A 2023 study by Ghosh et al 75 reported a 2.58‐fold increase in the odds of postoperative infection (ie, bloodstream infection, surgical site infection, ventilator‐associated pneumonia [ P =0.040]) associated with exclusive infant formula, compared with exclusive HM, for infants undergoing cardiac surgery at a single center in India. This study, however, is limited in that infants in the exclusive HM group were substantially older (ie, median 60 days versus 15 days) and underwent less complicated procedures, on average.…”
Section: Discussionmentioning
confidence: 99%
“…HM has been associated with lower rates of sepsis 16,17,19,30,76,77 and infection 32 for preterm infants and infants with surgical gastrointestinal anomalies, with protective mechanisms likely similar to those previously described for NEC (eg, reduced gut dysbiosis with subsequent lower risk of pathogenic gut bacteria translocation 78 ). A 2023 study by Ghosh et al 79 reported a 2.58 times increase in the odds of postoperative infection (ie, bloodstream infection, surgical site infection, ventilator-associated pneumonia; p = 0.040) associated with exclusive infant formula, compared to exclusive HM, for infants undergoing cardiac surgery at a single center in India.…”
Section: Sepsis and Infectionmentioning
confidence: 99%
“…The report from Ghosh and colleagues published in this issue of World Journal for Pediatric and Congenital Heart Surgery is a welcome addition. 9 In this prospective observational single-center study from Amrita Institute of Medical Sciences and Research Centre, the investigators compared early postoperative outcomes for 270 patients less than four months old at the time of surgery, fed with expressed breastmilk (EBM), infant formula, or combined EBM and infant formula after congenital heart surgery over a 16-month period. The exclusive EBM group had the lowest postoperative infection rates, lowest ventilation duration, shortest ICU stay, and shortest time to achieve postoperative oral feeding.…”
mentioning
confidence: 99%